Biglycan Inhibits Capsaicin-Induced Substance P Release by Cultured Dorsal Root Ganglion Neurons. (September 2016) - Shi, Peng; Chen, Er-Yun; Cs-Szabo, Gabriella; Chee, Ana; Tannoury, Chadi; Qin, Ling; Lin, Han; An, Steven; An, Howard S.; Zhang, Yejia
ABSTRACT: Objective: The purpose of this study was to examine the inhibitory effects of biglycan on substance P release from cultured sensory neurons in response to capsaicin. Study Design: In vitro study of cultured primary sensory neurons from the rabbit dorsal root ganglion (DRG). We interrogated the culture system function with capsaicin. Biglycan is an important structural component of the intervertebral disc that may regulate growth factors and inflammatory mediators. We tested the hypothesis that biglycan inhibits substance P release in response to capsaicin. Results: The DRG cultures were shown to contain both neurons and astrocytes by immunostaining using antibodies recognizing neuron and glial cell markers. Cultured DRG cells respond to capsaicin in a dose- and time-dependent manner (capsaicin dose ranges from 5 to 500 μmol/L; stimulation time ranges from 0 to 60 minutes). The neurons preincubated with biglycan released 27% less substance P compared with neurons without biglycan (n = 4, P = 0.036). Conclusion: We have established a DRG cell culture system, which contains both sensory neurons and the supporting astrocytes. Biglycan, an inhibitor of substance P release by DRG cultures, may serve as an ingredient in intradiscal injectables to reduce back pain.